Strategi Guru Untuk Meningkatkan Kemampuan Membaca Permulaan Pada Siswa Kelas I SD di Masa Pandemi - Ilman Hanafi Destian; Dwiana Asih Wiranti; Aan Widiyono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The ability to read is one of the aspects of language that students in elementary school need to learn. The success of students in learning is influenced by the mastery of students' reading skills at the beginning level. The impact of the Covid-19 virus makes it difficult for grade 1 elementary school students to read so that they have difficulty understanding the material presented by the teacher through online learning. For this reason, steps were taken to implement the strategy by holding